Penerapan Time And Motion Study dalam Upaya Perbaikan Waktu pada Proses Produksi CV. JM PUTRA - Andito Dwi Rangga; Urip Aji Trio; Alif Ranaya Syahadatan Gunawan; Budiharjo Budiharjo (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to analyze work time efficiency and determine standard time in the furniture production process at CV. JM Putra using the Time and Motion Study method. The background of this study stems from the problem of low production time efficiency due to suboptimal work methods, ineffective work area layout, and a lack of systematic work time measurement. The research was conducted quantitatively and descriptively through direct observation, interviews, and time measurements using a stopwatch for the table production process, which consisted of five main activities. The results showed that the average total cycle time for one table unit was 347.25 minutes, with the activity of assembling the table frame being the longest activity at 120.13 minutes or about 34.6% of the total working time. After performance assessment and the addition of a 15.5% allowance factor, the standard time was obtained at 129.03 minutes. These results indicate that the activity of assembling the table frame is the most critical point that affects production efficiency. The implications of this study show the importance of improving work methods, area layout, and operator training to increase labor productivity. The application of standard time measurement results can be used as a basis for setting work standards, production capacity planning, and a more objective labor incentive system.